KEPASTIAN HUKUM REGULASI REPURCHASE AGREEMENT DALAM KONSTRUKSI HUKUM INDONESIA - Dhafa Adia (2022)
The purpose of writing this scientific article is to describe the different regulatory arrangements on repurchase agreement transactions regulated through the Capital Market and Financial Institution Supervisory Agency Regulations and Financial Services Authority Regulations. The transfer of Bapepam-LK to OJK does not abolish the repo arrangement that has been in effect previously, so these two regulations still exist to this day, but have differences in their technical arrangements which will certainly have an impact on repurchase agreement transaction actors in the capital market. The type of research used in this research is normative juridical with a statutoryapproach and a conceptual approach, by collecting data using secondary data from primary, secondary and tertiary legal materials through library research, after collecting it will be analyzed qualitatively. Once collected, it will be analyzed qualitatively. The results of this study discuss the inconsistencies of the articles in the repo transaction regulations regulated through Bapepam-LK and the Financial Services Authority Regulations. The emergence of disharmony of the rule of law is caused by several influencing factors that have a negative impact on repo transaction actors in the capital market. One solution that must be done so that the disharmony of laws and regulations does not continue to occur is one of them by harmonizing the legal rules with one another so that they can provide legal certainty for repo transaction actors in the capital market. Keywords : Legal Certainty; Repurchase Agreement; Financial Services Authority Regulations; Capital Market and Financial Institution Supervisory Agency